Transcriptional regulation of the vitellogenin gene through a fecundity‐related single nucleotide polymorphism within a GATA‐1 binding motif in the brown planthopper, Nilaparvata lugens. Issue 3 (27th February 2018) - Sun, Z.‐X.; Kang, K.; Cai, Y.‐J.; Zhang, J.‐Q.; Zhai, Y.‐F.; Zeng, R.‐S.; Zhang, W.‐Q.
Abstract: Identifying the Single Nucleotide Polymorphisms (SNPs) with functions in insect fecundity promises to provide novel insight into genetic mechanisms of adaptation and to aid in effective control of insect populations. We previously identified several SNPs within the vitellogenin ( Vg ) promoter region between a high‐fecundity population (HFP) and a low‐fecundity population (LFP) of the brown planthopper, Nilaparvata lugens Stål (Hemiptera: Delphacidae). Here, we found that an A‐to‐T (HFP allele to LFP allele) transversion at nucleotide −953 upstream of Vg in a Nilaparvata lugens GATA‐1 ( Nl GATA‐1) binding motif is associated with the level of Vg transcription. We also characterized Nl GATA‐1, containing a double CX2 CX17 CX2 C zinc finger, which has been implicated in the activation of Vg gene expression. Knockdown of the NlGATA‐1 gene results in a reduced basal level of expression of the Vg gene and fewer offspring of N. lugens in vivo, whereas overexpression of NlGATA‐1 in cells increased Vg promoter activity. Moreover, upon cotransfection with Nl GATA‐1 expression vector, the luciferase activities of Vg reporter vectors with the A allele were significantly higher than those with the T allele. These findings support a mechanism in which a SNP within the promoter of Vg is associated with the level of Vg transcription by altering the binding activity of Nl GATA‐1 and subsequently affecting fecundity in N. lugens .